Trinity Church under construction, Boylston Street, Copley Square, ca. 1874 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking southwest of the construction area of Trinity Church. The street running diagonally behind the building is Huntington Avenue. The buildings in the background are on Dartmouth Street. 5 1/2 x 8 1/8 Photographs